1993
DOI: 10.1002/1520-6297(199305)9:3<247::aid-agr2720090306>3.0.co;2-8
|View full text |Cite
|
Sign up to set email alerts
|

A factor analysis of the product and service attributes offered by western nursery stock suppliers

Abstract: Survey data from 311 garden centers, landscapers, and combined garden centerhandscaping firms in selected western US trade centers were factor analyxed. Six first-order factors of product and service attributes were identified: plant selection, product information, supplier services and knowledge, advertising and promotion, plant quality, and ordering services. These six firstorder factors were collapsed into three second-order factors: buyer-oriented services, buyer perception of supplier reputation, and sale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1995
1995
2015
2015

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…A study of the nursery trade for landscapers and retailers in the US indicated that the dominant characteristic of buyer preference was plant quality (Foltz et al 1993). Other factors which significantly influenced buyer behaviour were offering a diversity of plant species, plant size, origin of the plant, plant price, and the option to pay for purchases with cash.…”
Section: Intra-eu Tradementioning
confidence: 99%
“…A study of the nursery trade for landscapers and retailers in the US indicated that the dominant characteristic of buyer preference was plant quality (Foltz et al 1993). Other factors which significantly influenced buyer behaviour were offering a diversity of plant species, plant size, origin of the plant, plant price, and the option to pay for purchases with cash.…”
Section: Intra-eu Tradementioning
confidence: 99%